HISTORY OF HISTORIOGRAPHY FROM A SLIGHTLY COSMOPOLITAN POINT OF VIEW1. Issue 2 (May 2016) - Malerba, Jurandir
ABSTRACT: Under review here are three works of different formats and scopes, each addressing questions of theory of history and the history of historiography. First, the mature work of Ignacio Olábarri Gortázar, published by the University Press of Salamanca, where he is now an emeritus professor, collects pieces written over a period of fifteen years that deal with matters related to his field of research in social labor history and other methodological and historiographical issues. Second, Fernando Sánchez Marcos seeks to offer an introductory book on the most noteworthy theoretical and historiographical issues of the twentieth century. Third, the volume from Jaume Aurell (Spain), Peter Burke (England), Catalina Balmaceda, and Felipe Soza (both from Chile) is a general handbook of historiography addressed primarily to students. All have their strengths and weaknesses. The most striking weakness is a persistent limitation of the field of vision, which is restricted to a European/Western (Francophone, Anglophone) cultural universe.